Kajian Struktur dan Fungsi Bahasa Pada Produk Makanan dan Minuman Iklan Televisi Berdasarkan Analisis Wacana - Azra Batrisyia; Dzakiyah Mega Wangi; Ernisa Hidayah; Mustika Wati Siregar (BADAN PENERBIT STIEPARI PRESS, 2024)
The highest position at the linguistic level is discourse. Discourse is said to be the most complete unit of language. Discourse analysis is the study of message structure in communication. This research describes the structure and function of food and beverage products in television advertising. Researchers use a discourse analysis approach, with a qualitative research type. This research method is descriptive analysis, using listening and note-taking techniques. The data source in this research was obtained through food and drink advertisements. The research results show that there is an advertising structure consisting of the main points of the advertisement consisting of four propositions, namely: (a) providing benefits for potential consumers; (b) the title and subtitle sentences are product brands with foreign terms or seem unique; (c) question sentences to consumers; (d) orders to potential consumers to do something. The explanatory items consist of three propositions, namely: (a) subjective reasons; (b) objective reasons; (c) a mixture of subject and objective reasons. The closing points of the advertisement were developed into: hard techniques, soft techniques, and a mixture of hard and soft techniques. Apart from that, researchers obtained language functions which include: information function, persuasive function, and image building function for a product.